Realizing stretch goals via exploratory bricolage: The case of Chinese entrepreneurial firms - Zhou, Shihao; Li, Peter Ping; Yang, Monsol Zhengyin (Taylor and Francis, 2019)
Bricolage has been brought into entrepreneurship and innovation research since the early 2000s. Bricolage challenges the research-based view that the firm-specific competitive advantages are rooted in the ownership of valuable, rare, inimitable, and non-substitutable resources. The insight of exploratory bricolage is that innovators can conduct radical or disruptive innovations by reexamining the taken-for-granted assumptions. This chapter investigates how companies with severe resource constraints achieve stretch goals via ingenious methods. The Chinese style or pattern of innovation is argued to be unique in several aspects, and one of them is highlighted as a compositional approach. A fundamental paradox of entrepreneurship is the tension between a passionate entrepreneur’s stretch goal, i.e., goals that are seemingly impossible given his or her current resources or capabilities, and the serious lack of access to required resources or capabilities.